Evaluation of Nitrite Concentration in Edible Bird’s Nest (White, Yellow, Orange, and Red Blood) - Ningrum, Siti Gusti; Palgunad, Bagus Uda; Sasmita, Rochiman (UI Scholars Hub, 2022)
The color of edible bird’s nest is associated with its nitrite concentration, but this relationship remains inconclusive. This investigation aimed to evaluate the nitrite content in edible bird’s nest of four different colors: white, yellow, orange, and red blood. Fifty-eight edible bird’s nest samples were obtained from five swiftlet farmhouses in Borneo Island, Indonesia and analyzed for nitrite content using Genesys 30 visible spectrophotometer. Results showed that the dark-colored edible bird’s nests (yellow, orange, and red blood) had higher nitrite concentrations of 304, 317, and 309 ppm, respectively, compared with the white-colored one (15 ppm). Therefore, the color of edible bird’s nest was associated with its nitrite concentration. This study provided updated information about the nitrite concentration in edible bird’s nest of various colors.